Keanekaragaman Serangga Pada Tanaman Teh (Camellia Sinensis L. Kuntze) Di Ptpn VI Kayu Aro Kabupaten Kerinci - Deni Andisca; Hidrayani; Reflin; Zahlul Ikhsan (Jurnal Riset Perkebunan, 2021)
It is important to know the presence of insects in tea plants (Camelia sinensis) so that they can be managed properly so that they do not cause damage to plants. This research aimed to study the diversity of insects in the tea plantation of PTPN VI Kayu Aro, Kerinci District. The method was a survey with a systematic random sampling technique. Insect samples were taken at three locations with different heights, namely: location I (+1.401 m asl), location II (+1.550 m asl), and location III (+1.715 m asl). Samples were taken by using a vacuum and directly by hand. The results showed that the insect species found in each research location were not different and included to the medium diversity index with each diversity index value of 1,79; 1,90, and 1,74 for locations I, II, and III, respectively. The evenness index value at the research location is 0,86; 0,91; and 0,84 for each location. Location I, location II, and location III included to the high evenness index.